Reviews. Issue 3 (1st October 2019) - Gordon, Beverly; Brewster, Maureen; Divita, Lorynn; Hannel, Susan; Lascity, Myles Ethan; Lindholm, Christina; Delgado, Henry Navarro; Porter, Matthew; Seidl, Monika
House of Fashion: Haute Couture and the Modern Interior, Jess Berry (2018) London: Bloomsbury Visual Arts, 213 pp., black and white illustrations and colour plates, bibliography, index, ISBN 978-1-47428-340-3, p/bk, $31.95The Fashion Show: History, Theory and Practice, Gill Stark (2018) 1st ed., London, New Delhi, New York and Sydney: Bloomsbury Visual Arts, 216 pp., ISBN 978-1-47256-848-9, p/bk, $27.96Fashioning Horror: Dressing to Kill On Screen and in Literature, Julia Petrov and Gudrun D. Whitehead (eds) (2018) London: Bloomsbury Academic, 234 pp., ISBN 978-1-35003-618-5, h/bk, £85, $114Fashion Cities Africa, Hannah Azieb Pool (ed.) (2016) Bristol and Chicago: Intellect, 143 pp., ISBN 978-1-78320-611-7, p/bk, $28.50Fashion Journalism: History, Theory and Practice, Sanda Miller and Peter McNeil (2018) New York: Bloomsbury, 172 pp., ISBN 978-1-47253-581-8, p/bk, $28.76; ISBN 978-1-47252-017-3, h/bk, $84.60Colors in Fashion, Jonathan Faiers and Mary Westerman Bulgarella (eds) (2017) London: Bloomsbury, 227 pp., ISBN 978-1-35007-740-9, p/bk, $37.95Fashioning Professionals: Identity and Representation at Work in the Creative Industries, Leah Armstrong and Felice MCDOWELL (EDS) (2018) London, Oxford, New York, New Delhi and Sydney: Bloomsbury, 224 pp., ISBN 978-1-35000-186-2, h/bk, $88.00Fashion History: A Global View, Linda Welters and Abby Lillethun (2018) London and New York: Bloomsbury, 195 pp., ISBN 978-1-47425-476-2, p/bk, $91.00Fashioning the Victorians: A Critical Sourcebook, Rebecca N. Mitchell (ed.) (2018) London, New York, Oxford, New Delhi and Sydney: Bloomsbury Visual Arts, 245 pp., ISBN 978-1-35002-339-0, h/bk; ISBN 978-1-35002-340-6, p/bk; ISBN 978-1-35002-338-3, ePub; ISBN 978-3-50023-413, e-book, $94.00